Are Believers Happier than Atheists? Well-being Measures in a Sample of Atheists and Believers in Puerto Rico - González-Rivera, Juan (2019)
Currently, not much has been written about the empirical psychological well-being of the atheist community in Puerto Rico and Latin America. The objective of the present study is to analyze if there are statistically significant differences in the levels of life satisfaction and psychological flourishing between believers in God and self-identified atheists. For this purpose, a sample of 821 participants (415 believers and 406 atheists) ranging from the ages of 19 to 85 years was selected. The results show that there is a slight average difference regarding life satisfaction and psychological flourishing between these groups; however, the difference is not substantial enough to ensure that believers in God or atheists have a better quality of life. Both believers and atheists exhibit high levels of life satisfaction and psychological flourishing. This study provides empirical evidence to demystify certain traditional assumptions about the supremacy of religious beliefs over secular convictions or vice versa. We hope that these findings create social awareness and could be used as a basis for future research concerning the population of non-believers.